(untitled) (JURNAL PROTEKSI KESEHATAN, 2022)
Dragon fruitskin (Pandanus sp) and red spinach (Alternanthera amoena Voss) contain beta carotene which produces natural orange-red pigments that is widely used as a coloring agent worm eggs in soil. This study aims to determine the optimal ratio of red dragon fruit skin and red spinach stems juice to identify Ascaris lumbricoides eggs. The juice ratio was 1:1, 1:2, 1:3 and 1:4, with 2% eosin and distilled water for positive and negative control, respectively. The results show that the dragon fruit peel juice provide a more reliable result in identifying A. lumbricoides eggs which give a contrasting field of view, worm eggs absorbed color, and the egg parts were clearly visible, close to the result providing by the positive control. Meanwhile, pure juice of red spinach stems resulted in a less contrasting field of view, worm eggs did not absorb color, and the eggs were not clearly visible. In conclusion, the red dragon fruit peel can identify the Ascaris lumbricoides worm eggs and can be developed to be a reagent to identify the eggs